2018
DOI: 10.1177/0271678x18758548
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral perfusion and compensatory blood supply in patients with recent small subcortical infarcts

Abstract: Hypoperfusion is the typical perfusion pattern associated with recent small subcortical infarcts of the brain, but other perfusion patterns may be present in patients with these infarcts. Using CT perfusion, we studied 67 consecutive patients who had a small subcortical infarct at a follow-up MRI study to investigate the correlation between the perfusion pattern and the clinical and radiological course. On CT perfusion map analysis, 51 patients (76%) had focal hypoperfusion, 4 patients (6%) had hyperperfusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…We speculated that perfusion abnormalities demonstrated on the ASL maps in the acute phase in our series may be explained by the presence of reduced blood supply in the setting of nonocclusive hypoxic-ischaemic encephalopathy. 24,[29][30][31] Finally, we acknowledge the several limitations of this study, most notably related to the retrospective study design and to the small number of patients included. However, the latter reflects the rarity of CLN in clinical practice, especially in the acute phase in the postoperative setting.…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that perfusion abnormalities demonstrated on the ASL maps in the acute phase in our series may be explained by the presence of reduced blood supply in the setting of nonocclusive hypoxic-ischaemic encephalopathy. 24,[29][30][31] Finally, we acknowledge the several limitations of this study, most notably related to the retrospective study design and to the small number of patients included. However, the latter reflects the rarity of CLN in clinical practice, especially in the acute phase in the postoperative setting.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 However, recent studies using dynamic 4-dimentional angiography derived from perfusion CT acquisitions have visualized collateral flow in SSIs, with compensatory blood supply to the ischemic area from adjacent perforator arteries. 20,28 Moreover, CSVD has now been recognized to reflect whole-brain endothelial dysfunction, which is strongly correlated with loss of brain reactivity, and is reflected by a more globally compromised CBF. 29 Therefore, the higher hemispheric CBF seen in our study might also reflect better 'collateral reserve' in patients with SSIs, and hence the association with better clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this sample size is comparable with similar studies. 20,28 Second, the perfusion changes before or after rtPA was measured in different patients with only one perfusion imaging scan. It would be ideal to perform perfusion imaging before and after rtPA, but this is not considered routine care due to radiation dose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forster et al first observed anterograde and retrograde collaterals in acute lacunar infarction using 4D dynamic susceptibility contrast (DSC) MR perfusion [13]. Rudilosso et al used CT perfusion to demonstrate that there was delayed compensatory collateral supply in recent SSI [14]. However, they did not show clinically significant differences between the collateral flow patterns.…”
Section: Introductionmentioning
confidence: 99%